Oil-water interfacial tensions of silica nanoparticle-surfactant formulations - Al-Anssari, S.; Wang, Shaobin; Barifcani, Ahmed; Iglauer, S. (2017)
© 2017 Carl Hanser Publisher, Munich. The implementation of nanotechnology in all industries is one of most significant research fields. Nanoparticles have shown a promising application in subsurface fields. On the other hand, various surfactants have been used in the oil industry to reduce oil/water interfacial tension and also widely used to stabilize the nano-suspensions. The primary objective of this study was to investigate the improvements of surfactants ability in term of inter facial tension (?) reduction utilizing addition of silicon dioxide nanoparticles at different temperatures and salinity. The pendant drop technique has been used to measure ? and electrical conductivity has been used to measure the critical micelle concentration (CMC). The synergistic effects of surfactant-nanoparticles, salt-nanoparticles, and surfactant-salt-nanoparticles on ? reduction and the critical micelle concentration of the surfactants have been investigated. Extensive series of experiments for ? and CMC measurements were performed. The optimum condition for each formulation is shown. We conclude that nanoparticles-surfactant can significantly reduce ? if correctly formulated.